ANALISA PENGARUH DIMENSI KUALITAS LAYANAN TERHADAP KEPUASAN PELANGGAN DALAM PENYEDIA JASA LOGISTIK – STUDI KASUS : PT. LBS SURABAYA - Agoes Junaedy (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2017)
Creating the excellence of the products is a must where competitiveness of service in logistic provider in giving satisfaction to valued customers. The main objective of the research is to determine the relationships amongst variables : personnel contact quality, timeliness, order discrepancy handling, ordering procedures as technical functions in logistic quality performance related to the customer satisfaction. The technique used in the analysis is done by structural equation model for obtaining the highest weights amongst variable used in the research, while measuring variables is by using a five-point likert-type Scale. The results of the research can be obtained by examining the effects of those variables stating that personnel contact quality has no substantial contributions on customer satisfaction, timeliness has substantial contributions on customer satisfaction, order discrepancy handling has substantial contributions on timeliness, order discrepancy handling has substantial contributions on customer satisfaction, ordering procedures has substantial contributions on customer satisfaction, personnel contact quality has no contributions on timeliness, and ordering procedures has substantial contributions on order discrepancy handling.